Pharmacists’ perceptions of their emerging general practice roles in UK primary care: a qualitative interview study - Butterworth, Jo (Br J Gen Pract, 2017)
BACKGROUND: UK general practice is experiencing a workload crisis. Pharmacists are the third largest healthcare profession in the UK; however, their skills are a currently underutilised and potentially highly valuable resource for primary health care. This study forms part of the evaluation of an innovative training programme for pharmacists who are interested in extended roles in primary care, advocated by a UK collaborative ‘10-point GP workforce action plan’. AIM: To explore pharmacists’ perceptions of primary care roles including the potential for greater integration of their profession into general practice. DESIGN AND SETTING: A qualitative interview study in UK primary care carried out between October 2015 and July 2016. METHOD: Pharmacists were purposively sampled by level of experience, geographical location, and type of workplace. Two confidential semi-structured telephone interviews were conducted — one before and one after the training programme. A constant comparative, inductive approach to thematic analysis was used. RESULTS: Sixteen participants were interviewed. The themes related to: initial expectations of the general practice role, varying by participants’ experience of primary care; the influence of the training course with respect to managing uncertainty, critical appraisal skills, and confidence for the role; and predictions for the future of this role. CONCLUSION: There is enthusiasm and willingness among pharmacists for new, extended roles in primary care, which could effectively relieve GP workload pressures. A definition of the role, with examples of the knowledge, skills, and attributes required, should be made available to pharmacists, primary care teams, and the public. Training should include clinical skills teaching, set in context through exposure to general practice, and delivered motivationally by primary care practitioners.